Land Use Change, Hydrological Responses and Water Balance of Upstream Ciujung Watershed - Nabilla Meilasari; Yayat Hidayat; Suria Darma Tarigan (Institut Pertanian Bogor, 2026)
Ciujung Watershed is an important land located in Banten Province, Indonesia. The Upstream Ciujung Watershed has seen numerous changes in land usage. Before implementing the best watershed management practices, we must first gather knowledge about the watershed's features. This report seeks to provide information about the characteristics of the Upstream Ciujung Watershed, covering land-use changes, hydrological responses, and water balance. Land use changes were analyzed using satellite imagery from 2016 and 2021, with changes traced using ArcGIS and Excel; hydrological response method for flow regime coefficient (FRC) and annual flow coefficient (AFC) in the 2012−2016 and 2017−2021 periods. Water balance was analyzed by calculating water demand in 2021 and availability water from 2012−2021. The study found that deforestation occurred between 2016 and 2021. Primary forest, secondary forest, and production forest area fell by 51 ha, 1,073 ha, and 3,119 ha, respectively, while dryland agricultural area increased with a mix of shrubs, plantations, and settlements, contributing to the alteration in the watershed. The FRC and AFC values from 2012 to 2016 were 49 (poor) and 0.32 (moderate). Meanwhile, the FRC and AFC for 2017–2021 were 60 (moderate) and 0.30 (moderate). The water balance of the Upstream Ciujung Watershed in 2021 indicates a water surplus of 663,739,545 m3/year, while the dry season in September shows a shortfall of −5,468,643 m3/month. Keywords: annual flow coefficient, flow regime coefficient, hydrological function, watershed management